Drivers, Uncertainties, and Scenarios of the Iranian Economic System - Mohammad Esmaeilzadeh; Mostafa Azari; Yousef Ramezani (International Journal of Management, Accounting and Economics, 2024)
Iran's economy is founded on three main sectors: cooperative, private, and governmental. Various key documents outline objectives for each sector, highlighting certain industries with unique advantages and capacities. These industries not only have strong interconnections with other sectors but also drive demand and contribute to economic growth. This study aims to analyze and present various potential futures for Iran's economy, adopting a holistic and comprehensive perspective. It explores the key factors shaping the economy, including constructive economic drivers, significant uncertainties, and potential future scenarios, considering various influential dimensions. The research employs a qualitative scenario-based approach, structured in eight stages. Data is gathered through interviews, expert panels, and the Delphi survey method, with analysis supported by Mac and Scenario software and a wizard tool. The study identifies primary economic drivers for Iran, including economic growth, oil dependency, the impact of economic sanctions, fundamental challenges, and the level of economic openness. While other factors like high unemployment, a small capital market, rent-seeking, weak infrastructure, and corruption significantly influence the economic landscape, they are not classified as primary drivers in this study. However, these elements will be considered in developing future economic scenarios. Also, in order to prioritize solutions to deal with economic threats, it should be said that using short-term methods in the programs and executive plans of the country's institutions will be the first step to deal with threats. At the same time, planning and using solutions of higher levels, respectively, can move the country step by step in terms of structure and institutions in the direction of resilience, invulnerability and regeneration.